Digital inclusiveness: global - Martins, Carolina; Opola, Felix; Schmitter, Petra; Dembélé, Moctar (International Water Management Institute, 2025)
The Multidimensional Digital Inclusiveness Index (MDII) was designed to address the lack of digital inclusiveness in Agri systems. It provides a structured framework to evaluate and enhance gender and social inclusiveness, ensuring equitable, accessible digital tools.